Occurrence of 15 Haplotypes of Linepithema micans (Hymenoptera: Formicidae) in Southern Brazil - Ramalho, Manuela Oliveira [UNESP]; Martins, C.; Campos, T. [UNESP]; Nondillo, A.; Botton, M.; Bueno, O. C. [UNESP] (Oxford University Press (OUP), 2017)
The ant genus Linepithema is widely known, thanks to the pest species Linepithema humile (Mayr), which is easily mistaken for Linepithema micans (Forel) due to their morphological similarity. Like L. humile, L. micans is associated to the main grapevine pest in Brazil, Eurhizococcus brasiliensis (Wille), also known as ground pearl. Therefore, the present study uses mtDNA fragments to expand the knowledge of haplotype diversity and distribution of L. micans in the state of Rio Grande do Sul (Brazil), to understand the genetic differences of the populations identified in this study. We identified 15 haplotypes of L. micans spread across different localities. Twelve of these haplotypes were new for the species. The high haplotype diversity uncovered in Rio Grande do Sul (Brazil) for this species was predictable, as L. micans is in its native environment. Additional studies that take gene flow into account may reveal interesting aspects of diversity in these populations.
Keywords: ground pearl; mitotype; Rio Grande do Sul